The Contagious Colors of Mumpley Middle School - DeWitt, Fowler; Montalvo, Rodolfo (New York : Atheneum Books for Young Readers, 2013)
When a mysterious illness sweeps through school, causing students to change color, sixth-grader scientist Wilmer Dooley tries to find the cause and cure.
Keywords: Science -- Juvenile fiction -- Methodology; Diseases -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Science -- Fiction -- Methodology; Diseases -- Fiction; Middle schools -- Fiction; Schools -- Fiction